Dysregulated lipids homeostasis disrupts CHAC1-mediated ferroptosis driving fibroblast growth factor receptor tyrosine kinase inhibitor AZD4547 resistance in gastric cancer - Jingwen Chen; Yedi Huang; Daocheng Zuo; Ruimin Shan; Songmao Li; Ran Li; Dong Hua; Qiang Zhan; Xudong Song; Yun Chen; Pei Ma; Ling Ma; et al. (Redox Biology)
Aims: This study investigates the mechanisms underlying acquired resistance to FGFR tyrosine kinase inhibitor (FGFR-TKI) in gastric cancer (GC), focusing on the interplay between ferroptosis and lipid metabolism of tumor cells. Methods: We constructed FGFR-TKI-resistant cell lines from GC cells. RNA sequencing was performed to identify differentially expressed genes (DEGs) related to ferroptosis and assess lipid metabolism in resistant cells. GC microenvironment lipid profile was characterized by HPLC-MS/MS lipidomics. The effects of CHAC1 and cholesterol synthesis modulation on ferroptosis and FGFR-TKI resistance were assessed using in vitro and in vivo models. Results: We found that FGFR-TKI can induce ferroptosis in FGFR-TKI-sensitive cells, while resistant cells exhibit decreased sensitivity to ferroptosis due to reduced CHAC1 expression, a key glutathione-specific degrading enzyme. Overexpression of CHAC1 enhances FGFR-TKI cytotoxicity. Additionally, cholesterol accumulation in resistant cells, associated with diminished stearic acid (SA) uptake, confers FGFR-TKI-induced ferroptosis resistance. In vivo studies show that CHAC1 overexpression or cholesterol synthesis inhibition can reverse FGFR-TKI resistance, which is dependent on ferroptosis. Conclusions: Dysregulated lipid homeostasis downregulated CHAC1-mediated ferroptosis, leading to FGFR-TKI resistance in gastric cancer. Overexpression of CHAC1 or inhibiting cholesterol synthesis presents promising therapeutic strategies to overcome FGFR-TKI resistance in GC.